THE ROLE OF THE AMAIBI IN THE LAI HARAOBA OF MANIPUR - Salam Shantibala Devi (International Journal of Research -GRANTHAALAYAH, 2018)
Lai Haraoba is an inseparable part of the cultural life of the Meiteis known as Manipuris in general. It has a dimorigin. Lai Haraoba is a ritual performed under strict rules and order with the objective to please various deities and ancients. During the ritual which may last five days or more, the creation of the world and humans is represented with dance and sing by the maibis accompanied by the pena music of the Maiba. The number of Maibis may vary from three to more than three where only one maiba or Amaiba is employed. There are numerous Umang lais thus to be pleased ritually once in a year. In fact, each place has its own different deity and some particular deities have been regarded as the guardian deity of a region in which all the villages falling inside that region will have to deserve the ritual of lai Haraoba for that particular deity only. This ritual is performed starting on an auspicious day during February to July in a year. The main objectives of Lai Haraoba are to please the deities sot that the area under whose protection becomes prosperous with less morality which also infers the idea of growth of population by reminding people to perform the act of procreation as a duty. This particular part or inducement is performed with beautiful lyrical dialogue on the last day of the ritual in the form of the chance meeting of Panthoibi and Nongpok Ningthou. A propose of what has been laid out above the objectives of the study are very clear. I will help in codifying women’s involvement in social and cultural life in Manipur along with its relevant ramifications in the present context. This paper attempt to discuss the importance role of Amaibis in umang Lai Haoba.